2016
DOI: 10.1007/s13524-016-0490-x
|View full text |Cite
|
Sign up to set email alerts
|

Same-Sex and Different-Sex Cohabiting Couple Relationship Stability

Abstract: Relationship stability is a key indicator of well-being, but most U.S.-based research has been limited to different-sex couples. The 2008 panel of the Survey of Income and Program Participation (SIPP) provides an untapped data resource to analyze relationship stability of same-sex cohabiting, different-sex cohabiting, and different-sex married couples (n = 5,701). The advantages of the SIPP data include the recent, nationally representative, and longitudinal data collection; a large sample of same-sex cohabito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 33 publications
3
66
1
Order By: Relevance
“…Evidence is mixed, however, as to whether same-sex couples exhibit similar levels of relationship stability when compared with different-sex married couple families (Kurdek, 2004(Kurdek, , 2006Lau, 2012;Manning, Brown, & Stykes, 2016), and no studies to date have examined family stability patterns among same-sex couples with children. Future efforts to collect the kind of data to fully explore these questions are imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is mixed, however, as to whether same-sex couples exhibit similar levels of relationship stability when compared with different-sex married couple families (Kurdek, 2004(Kurdek, , 2006Lau, 2012;Manning, Brown, & Stykes, 2016), and no studies to date have examined family stability patterns among same-sex couples with children. Future efforts to collect the kind of data to fully explore these questions are imperative.…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, recent studies have found that people in legally partnered same-sex relationships have higher relationship stability, more financial resources, and better health outcomes than couples who cohabit without legal recognition. 27,28 In addition, LeBlanc et al have hypothesized that lesbians and gay men may not experience the health benefits of marriage exactly as their heterosexual counterparts, as the individuals in these same-sex partnerships may experience individual-and/or couple-level stressors related to internalized homophobia, homoprejudice, and/or the lack of universal support for same-sex rather than opposite-sex marriage. 29 It is not possible to explore these ideas with this small sample; nevertheless, active studies as described above and future work may continue to find disparate health and other outcomes for legally recognized same-and opposite-sex partners-perhaps even future analyses with a larger sample that includes recently released CHIS data.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, this obligates us to compare same-sex couples only with heterosexual cohabiting couples. This was done in a recent study with British data conducted by Manning, Brown & Stykes (2014): it demonstrated that break up rates are greater for same-sex cohabiting couples, especially in the case of men. However, in reference to the factors associated with instability, there is considerable similarity between heterosexual and homosexual couples.…”
Section: Demographics Of Same-sex Couples: International Evidencementioning
confidence: 99%